A LONGITUDINAL INCREASE IN SLEEP HEALTH PROBLEMS IN MIDDLE ADULTHOOD PREDICTS EARLY MORTALITY. (20th December 2022) - Lee, Soomi; Mu, Christina; Wallace, Meredith; Andel, Ross; Almeida, David; Buxton, Orfeu; Patel, Sanjay
Abstract: Negative consequences of sleep health problems are common in middle-age but poorly understood. This study investigated multidimensional sleep health in middle adulthood and mortality risk. Participants from the Midlife in the United States Study reported sleep characteristics in 2004-2006 (T1; n=9, 640, Mage=52.72) and again in 2013-2016 (T2; n=4, 334). Deaths since each survey were logged. Multidimensional sleep health composite captured Regularity, Satisfaction, Alertness, Efficiency, and Duration. Cox regression adjusted for sociodemographics and known risk factors (BMI, smoking, depression/anxiety, diabetes, and hypertension) indicated that each unit higher sleep health problems at T1 was associated with 245% and 324% increase in hazard rates for all-cause (Hazard Ratio; HR=3.45, p<.001) and heart disease (HR=4.24, p<.001) mortality, respectively. Those with an increase in sleep health problems at T2 compared to T1 had a 182% increase in all-cause mortality risk (HR=2.82, p<.05), but not heart disease mortality risk. Improving sleep health may reduce early mortality risk.